CHEMICAL BONDING IN SULFIDE MINERALS - Vaughan D.J.; Rosso K.M. (My University, 2006)
An understanding of chemical bonding and electronic structure in sulfide minerals is central to any attempt at understanding their crystal structures, stabilities and physical properties. It is also an essential precursor to understanding reactivity through modeling surface structure at the molecular scale. In recent decades, there have been remarkable advances in first principles (ab initio) methods for the quantitative calculation of electronic structure. These advances have been made possible by the very rapid development of high performance computers. Several review volumes that chart the applications of these developments in mineralogy and geochemistry are available.